Subsitusi Protein Hewani dengan Tepung Kedelai dan Khamir Laut untuk Pakan Patin (Pangasius sp.) dan Kerapu Tikus (Cromileptes altivelis) - Mivida Febriani (Jurnal Perikanan Universitas Gadjah Mada, 2006)
The objective of this research was to know protein and energy digestibilities of marine yeast, as substitution for soybean meal in the ration of patin (Pangasius sp.) and humpback grouper (Cromileptes altivelis).This experiment used completely randomized design with four treatments in triplicates. The treatments were R1 (100% animal protein); R2 (90% animal protein+10% soybean meal); R3 (90% animal protein+5% soybean meal+5% marine yeast); and R4 (90% animal protein+10% marine yeast). The digestibility of protein in ration of patin was significantly different (P<0.01). Marine yeast in patin ration also improved the growth rate (P<0.05). Substitution soybean meal with marine yeast in ration of patin was not influence the energy digestibility and feed conversion ratio (FCR) (P>0.05). Rations with 5 and 10% of marine yeast improved energy and protein digestibility, growth rate and decreased the FCR. Digestibilities of protein and energy, growth rate and FCR in humpback grouper were significantly different (P<0.01) among treatments. Marine yeast in ration of humpback grouper increased digestibilities of protein and energy. However, substitution of animal protein with soybean meal and marine yeast decreased growth rate and improve FRC in humpback grouper.